High-low refractive index stacks for broadband antireflection coatings for multijunction solar cells. (15th March 2021) - Hou, GuoJiao; García, Iván; Rey-Stolle, Ignacio
Highlights: Thin alternating layers with high- and low refractive indices are used to produce broadband antireflection coatings. The performance of antireflection coatings for multijunction solar cells increases. The improvement of short circuit current density is up to 4.64% comparing to optimum double layer antireflection coatings. High improvement can be achieved even the deposition thickness error reaches 20%. Better performance at oblique angles of incidence is also attained. Abstract: Antireflection coatings are an interesting challenge for multijunction solar cells due to their broadband spectrum absorption and the requirement of current matching of each subcell. A new design for multijunction solar cell antireflection coatings is presented in this work in which alternative high and low index materials are used to minimize the reflection in a broadband (300–1800 nm). We compared the short circuit current density of high-low refractive index stacks designs with optimum double-layer antireflection coatings by considering two optical materials combinations (MgF2 /ZnS and Al2 O3 /TiO2 ) for the AM0 and AM1.5D spectra. The calculations demonstrate that for lattice-matched triple-junction solar cells and inverted metamorphic quadruple-junction solar cells, high-low refractive index stacks outperform the optimum double-layer antireflection coatings. The new design philosophy requires no new optical materials because only two materials are used and exhibits excellent performance in broadband spectra. The angle performance of these antireflection coatings is slightly better than classical double-layers whereas the analysis for thickness sensitivity shows that small deviations from deposition targets only slightly impact the performance of antireflection coatings. Finally, some technical solutions for depositing these high-low refractive index multilayers are discussed.